PERENCANAAN DAN ANALISA STRUKTUR RANGKA KURSI RODA ELEKTRIK BERKAPASITAS 80 KILOGRAM - Muhammad Abyan (2023)
Wheelchairs are one of the assistive devices that can facilitate mobility for people with special needs, whether they are individuals with disabilities or those who are currently injured. Typically, wheelchairs come in the form of manual wheelchairs, which require the assistance of another person to move them by pushing the wheelchair. However, with the advancement of time and technology, numerous studies have been conducted to design electric wheelchairs that can enhance ease of use. Taking into consideration the user's comfort while sitting in the wheelchair and utilizing a motor drive that can be operated according to the user's preference, it is essential to prioritize user safety in the design of such wheelchairs. This involves considering the materials used and the strength of the welding in connecting the metal components. As the first step in designing the wheelchair frame, the basic dimensions of the wheelchair will be determined to be suitable for the standard body posture of Indonesians, with a height between 150-170 cm and a maximum weight of 100 kg. With the advancement of technology, many ideas have been developed regarding wheelchairs, including the addition of several components to make the wheelchair more comfortable for the user. With proper arrangement of each facility, all production processes will proceed according to the predetermined schedule or time. The production process can be carried out effectively and efficiently